New varieties of shallots for Siberian conditions - O. V. Malykhina; E. V. Shishkina; S. V. Zharkova (Овощи России, 2021)
Relevance. Shallot is the universal culture in terms of its economically valuable indicators. Breeders in the south of Western Siberia carry out a lot of research work with the aim of creating varieties for Siberian conditions. Long-term studies have made it possible to select promising samples, and exceeding in their indicators the value of signs of released varieties.Materials and methods. The studies were carried out in field and laboratory conditions on the basis of the West Siberian Vegetable Experimental Station in the Priobskaya zone of the Altai Territory in 2016-2020. Research objects: samples of the nursery of competitive variety testing. Three appreciable forms No. 37, No. 39 and No. 48 passed competitive variety testing and, according to the results of the research, were transferred to the State Variety Testing.Results. Sample No. 39 showed marketable yield, which exceeded this indicator of the standard variety by 23.7% and amounted to 23.2 t/ha. The average weight of the sample No. 39 marketable bulbs was 29.0 g, for the standard variety it was 23.4 g. The content of vitamin C in the bulbs and leaves of the new sample exceeded these indicators of the standard variety by 0.3% and 0.53%, respectively. In 2018, sample No. 37 was transferred to the State Variety Testing. This sample belongs to the early maturing group. The bulbs yield of the new sample during all the years of testing significantly exceeded the yield of the standard variety and amounted to 20.3 t/ha (2016- 2018). Sample No. 48 was submitted to the State Variety Testing in 2020. The excess in bulbs yield of this sample was (2019-2020): 13,3%, leaves – 18,8%. In 2019, the Sharm variety was zoned and entered into the State Register of Breeding Achievements, in 2020 – the Chance variety. Sample No. 48 with the proposed name Pharaon has been undergoing the State Variety Testing since 2021.